2020
DOI: 10.1136/bmjgh-2020-002993
|View full text |Cite
|
Sign up to set email alerts
|

BCG skin reactions by 2 months of age are associated with better survival in infancy: a prospective observational study from Guinea-Bissau

Abstract: IntroductionReceiving Bacille Calmette-Guérin (BCG)-Denmark vaccine at birth has been associated with ~40% reductions in all-cause neonatal mortality. We evaluated determinants of BCG skin reaction characteristics by age 2 months and tested the association with subsequent mortality.MethodsProspective observational study amalgamating five trials providing BCG-at-birth that were conducted between 2002 and 2018 in Guinea-Bissau. The reaction status and size were evaluated at home-visits by 2 months of age among 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 39 publications
0
32
0
Order By: Relevance
“…The only difference between parents with and without a scar was age. Older parents were less likely to have a BCG scar, presumably reflecting improved BCG vaccination since it became general policy in the late 1980s as correct vaccination technique is one of the main determinants for developing a BCG scar [ 12 , 13 ]. Parental age in itself did not determine child survival in the first six weeks of life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The only difference between parents with and without a scar was age. Older parents were less likely to have a BCG scar, presumably reflecting improved BCG vaccination since it became general policy in the late 1980s as correct vaccination technique is one of the main determinants for developing a BCG scar [ 12 , 13 ]. Parental age in itself did not determine child survival in the first six weeks of life.…”
Section: Discussionmentioning
confidence: 99%
“…Field assistants were unaware of the hypothesis regarding parental BCG scars. We have previously shown that a BCG scar is an indicator for a correctly applied BCG vaccine[ 10 , 12 , 13 ] and its use, instead of reported BCG vaccination, overcomes possible problems with recall bias.…”
Section: Methodsmentioning
confidence: 99%
“…Upon switching to the late strain BCG Glaxo in 1978, that rate decreased to 6.4 per 100,000 2, 24 . Conversely, in phase one of a randomized control trial where BCG Danish was compared with BCG Russia, lymphadenitis was reported in 6 out of 582 patients given BCG Danish and one out of 575 patients given BCG Russia 28 . In this study, 6 out of 10 BCG isolates were early strains, presumably BCG Russia.…”
Section: Discussionmentioning
confidence: 97%
“…BCG strains differ from one another by genetic deletions, SNPs, and duplications ( 15 ). It has been suggested that some BCG strains may be associated with a higher rate of adverse events ( 2 , 14 16 ). This possibility is of particular interest in India, where both an early and a late BCG strain are currently in use.…”
Section: Discussionmentioning
confidence: 99%
“…Given the increased data on M. tuberculosis SNPs and the availability of real-time PCR reagents that enable multiplexed analyses, we developed a two-step real-time PCR assay to rapidly identify BCG from a bacterial culture or directly from infected tissue. The two steps were designed to (i) identify BCG from other members of the MTBC and (ii) differentiate between early and late strains of BCG, something of interest in India, where two different BCG strains (BCG Russia and BCG Danish) with potentially different rates of adverse events are in use ( 2 , 14 16 ). This assay was validated on 19 clinical isolates previously collected at Christian Medical College in Vellore, India, and our results suggest that the use of this assay may better inform patient management and enable BCG vaccine pharmacovigilance.…”
Section: Introductionmentioning
confidence: 99%